Schiff Base modified on CPE electrode and PCB gold electrode for selective determination of silver ion - Piyawan Leepheng; Songwut Suramitr; Darinee Phromyothin (My University, 2017)
The schiff base was synthesized by 2,5-thiophenedicarboxaldehyde and 1,2,4-thiadiazole-3,5-diamine with condensation method. There was modified on carbon paste electrode (CPE) and Printed circuit board (PCB) gold electrode for determination silver ion. The schiff base modified electrodes was characterized by atomic force microscopy (AFM) and scanning electron microscopy (SEM), respectively. The electrochemical study was reported by cyclic voltammetry method and impedance spectroscopy using modified electrode as working electrode, platinum wire and Ag/AgCl as counter electrode and reference electrode, respectively. The modified electrodes have suitable detection for Ag+. The determination of silver ions using the modified electrodes depended linearly on Ag+ concentration in the range 1×10-10 M to 1×10-7 M, with cyclic voltammetry sensitivity were 2.51×108 μAM-1 and 1.88×108 μAM-1 for PCB gold electrode and CPE electrode, respectively, limits of detection were 5.33×10-9 M and 1.99×10-8 M for PCB gold electrode and CPE electrode, respectively. The modified electrodes have high accuracy, inexpensive and can applied to detection Ag+ in real samples.
Keywords: Palladium-hydrogen electrode; Quinhydrone electrode; Glass electrode; Auxiliary electrode; Carbon paste electrode; Chemically modified electrode; Analytical Chemistry and Sensors